Prospects for the Use of Amaranth Grain in the Production of Functional and Specialized Food Products - Dana Toimbayeva; Saule Saduakhasova; Svetlana Kamanova; Amirsana Kiykbay; Sayagul Tazhina; Indira Temirova; Marat Muratkhan; Bakhyt Shaimenova; Linara Murat; Dina Khamitova; Gulnazym Ospankulova (Foods)
This review is dedicated to exploring recent advancements in the study of amaranth grain and presents research primarily on Amaranthus species such as Amaranthus cruentus, Amaranthus hypochondriacus, and Amaranthus caudatus, and to a lesser extent Amaranthus hybridus, Amaranthus mantegazzianus, Amaranthus muricatus, Amaranthus tuberculatus, Amaranthus viridis, Amaranthus spinosus, and Amaranthus tenuifoliu. Amaranth (Amaranthus spp.) is a promising, high-yield pseudocereal crop with significant commercial potential for developing functional food products. It contains a wide range of bioactive compounds, including squalene, tocopherols, phenolic compounds, phytates, and vitamins, which possess important physiological properties. Amaranth grain is characterized by high levels of starch, proteins, minerals, and dietary fiber. Moreover, amaranth proteins are distinguished by a balanced amino acid composition and exhibit greater resistance to external factors compared to animal-derived proteins. Grains of amaranth are free of gliadin, making it a valuable nutritional source for individuals with celiac disease, an immune-mediated disorder. Unlike traditional cereals, where prolamins and glutelins dominate the protein composition, the proteins of pseudocereals like amaranth primarily consist of albumins and globulins. The processing methods of amaranth grain influence their quantitative and qualitative composition, often significantly improving their physicochemical, antioxidant, functional, and rheological properties. This work provides a detailed analysis of amaranth’s chemical composition and bioactive components, along with its evaluation of therapeutic and preventive properties. Amaranth protein fractions (albumin, globulin, and glutelin) and squalene exhibit increased antioxidant activity, contributing to notable resistance to radiation and X-ray exposure. Bioactive compounds such as phytol, α-tocopherol, and a lunasin-like peptide (AhLun) with potential anticancer properties have also been identified in amaranth. Furthermore, six bioactive peptides were isolated and identified from amaranth, which, according to predictive models, demonstrate a high capacity to inhibit angiotensin-converting enzyme (ACE) activity, suggesting potential hypotensive effects. Certain amaranth peptides are considered promising functional food ingredients for the prevention and comprehensive treatment of conditions such as diabetes, inflammatory bowel diseases, hypercholesterolemia, cardiovascular diseases, and obesity. Amaranthus spp. and its processed products hold significant interest for the development of innovative food products, contributing to the expansion of their range and enhancement of nutritional value.